COMPARISON OF HEMODYNAMIC STABILITY WITH CISATRACURIUM AND ATRACURIUM IN PATIENTS WITH LOW EJECTION FRACTION UNDERGOING CORONARY ARTERY BYPASS GRAFTING - Mehwish Naseer (Army Medical College Rawalpindi, 2020)
Objective: To compare the hemodynamic stability with cisatracurium and atracurium in patients with low ejection fraction undergoing coronary artery bypass grafting.